PENGARUH LOCUS OF CONTROL, JIWA KEWIRAUSAHAAN, DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA - Deby Wahyu Indri Oktavia; Lilik Sri Hariani; Waluyo Edi (Jurnal Riset Pendidikan Ekonomi, 2017)
The study aimed to determine the effect of locus of control, entrepreneurial spirit, and entrepreneurial motivation influence on the entrepreneurial interest. This research is ex post facto. Population in this study was students of SMA Kristen Petra Malang as many as 83 students with boring sampling. Data were collected by questionnaire. Analyzed by using the multiple linear regression analysis. The result of this research show that 1) There is a significant effect locus of control, entrepreneurial spirit, and entrepreneurial motivation on interest in entrepreneurship, 2) There is a negative and significant effect locus of control on interest in entrepreneurship, 3) There is a positive and significant effect entrepreneurial spirit on interest in entrepreneurship, 4) There is a negative and significant effect entrepreneurial motivation on interest in entrepreneurship.